Periférikus fejlődés, szerkezetátalakítási törekvések : Baranya megye és az államszocialista iparpolitika - Lux, Gábor (Közép-Európai Közlemények, 2010)
In the socialist period, the economic welfare of Baranya County was tied to industrial development. Previously characterised by light industry, metallurgy’s needs for black coal and coke initiated a profound transformation within the county, which resulted in the dominance of the extractive sector and associated activities. Development in the period was overwhelmingly directed by central interests, leading to an economic structure that, while nominally “developed” by contemporary standards, showed structural imbalances from an early date. Local development policy recognised the relevance of economic diversification as early as the 1960s, but could not achieve fundamental change within the framework of the socialist planning system. With the changing demands of the national and world economy, the economic milieu of Baranya gradually became outdated, and already showed symptoms of structural decline before systematic change. Based on research in the county archives, this paper outlines the role of local and national authorities in socialist industrial policy, and analyses development concepts aimed at enacting change within a declining region, from the reforms of 1965 and 1969 to the failed transformation attempts in 1979 and 1984. The analysis is accompanied by an overview of development processes within the economy and the ultimate consequences: widespread de-industrialisation and the emergence of a (relatively weak) service-based economy.